Analysis of Reconstructed Modified Symmetric Teleparallel f(Q) Gravity - Myrzakulov, N.; Shekh, S. H.; Mussatayeva, A.; Koussour, M. (Frontiers in Astronomy and Space Sciences, 2022)
The existing analysis reports a reconstruction scheme of the newly proposed gravity say $f(Q)$ gravity through the scale factor of the form $a(t)=a_{0} t^{n}=\frac{1}{1+z}$ by describing the power-law cosmology. The reconstructed $f(Q)$ gravity models disclosed how this modified gravity model is capable to replicate dissimilar epochs of the cosmological history. Also, the reconstructed $f(Q)$ gravity models are castoff to develop the expressions for density and pressure and the equation of state parameter. I reconstruct two cases of interacting fluid scenario ghost and pilgrim dark energy with pressureless dark matter. The physical behavior of the models is talked over the evolution of the Universe is accelerated. Moreover, the well-known cosmological planes i.e., ($ω_{D}- ω^{′}_{D}$) and $(r-s)$ constructed for our models, also include a comparison of our findings of these dynamical parameters with observational constraints. It is also quite interesting to mention here that the results of the equation of state parameter, ($ω_{D}- ω^{′}_{D}$) and $(r-s)$-planes coincide with the modern observational data.